An integrated methodology for dynamic risk evaluation of deepwater blowouts. (January 2022) - Zhu, Jingyu; Chen, Guoming; Yin, Zhiming; Khan, Faisal; Meng, Xiangkun
Abstract: Offshore drilling operations face technological and operational challenges combined with harsh environmental conditions. The well blowouts are the most feared offshore process operational accident. Many methodologies have been proposed to assess the blowout risk. Most of these studies consider the risk factors' independence and focus on a specific drilling life cycle stage. This study presents an integrated methodology that considers the interaction among the drilling risk factors and assesses the blowout risk throughout the deepwater drilling operation's lifecycle. This integrated methodology is developed based on the index-based risk evaluation system, which comprises hazard identification, interaction analysis, indices weights, and risk evaluation. The Decision Making Trial and Evaluation Laboratory method is used to identify and assess risk factors' interaction. The uncertainty associated with the data is addressed using the Z-numbers method. The risk indices are dynamic to capture the hazards during the lifecycle of the drilling operation. The application of the methodology is tested on a deepwater drilling operation. The application demonstrates the methodology's effectiveness in assessing and evaluating blowout risk during the drilling operation lifecycle. Highlights: An index-based dynamic risk assessment methodology for deepwater blowouts is proposed. Underlying interdependency and interactions among risk factors are revealed by the DEMATEL analysis. The uncertainty credibility of the experts' evaluation is resolved using the Z-numbers method.